Use of food carbohydrates towards the innovation of plant-based meat analogs. (November 2022) - Huang, Mingfei; Mehany, Taha; Xie, Wenfeng; Liu, Xinran; Guo, Shuntang; Peng, Xingyun
Abstract: Background: In recent years, the market value of plant-based meat analog (PMA) foods has reached US $ 7.9 billion. The development of PMA products has become an important strategy for human beings to cope with the shortage of food and protein supply and the transformation of sustainable food. In the past, a large number of literatures have reported the manufacturing process and application technology of key PMA raw ingredients (e.g., textured protein). However, very few review studies have addressed the important role of food carbohydrates in this novel future food. Scope and approach: In this review, the general forms of carbohydrates and their impact on the textural and sensory qualities of current PMA were introduced. The potential opportunities for carbohydrates in addressing the future innovation needs of PMA foods were discussed. Key Findings and Conclusions: Food carbohydrates are widely used in PMA products due to their diverse structures and unique techno-functionality. In sum, carbohydrates play critical roles in improving the texture of PMA, promoting fibrillation of textured proteins, mimicking animal skin and connective tissue, acting as the fat or fat tissue substitute, and producing color, flavor, and aroma. This review creates a novel demand of carbohydrate-based ingredients for PMA formulation. Graphical abstract: Image 1 Highlights: Carbohydrates show great potentials in the innovation of plant-based meat analogs. Carbohydrates enhance the texture and sensory quality of plant-based meat analogs. Carbohydrates facilitate in the fabrication of fibrous protein extrudate. Carbohydrates are potentially used to simulate animal fat and connective tissues. Novel applications of carbohydrate in plant-based meat analogs were discussed.